Analisis Tata Kelola Arsip pada Bagian Tata Usaha Sekolah Tinggi Teknik Lingkungan (STTL) Mataram - Suryaningsih Suryaningsih; Nurwahidah Nurwahidah; Iswan Iswan; Dewi Rispawati (Departement of Mathematics Education, 2024)
This research is entitled Analysis of Archives Governance in the Administration Section of the Mataram College of Environmental Engineering (STTL), which aims to determine archival governance in the Administration Section of the Mataram College of Environmental Engineering (STTL). In this research, the Qualitative method is used, which is descriptive analysis, by collecting data in such a way, grouping it, then organizing it and connecting it with theories that are relevant to the problem and then drawing conclusions. The data sources in this research are primary data and secondary data as well as data collection techniques in this research, using documentation, observation and interviews. Based on the results of research that has been carried out regarding Archives Management in the Administration Section of the Mataram Environmental Engineering College, it can be concluded that: Simplicity of archiving, maintenance and safeguarding, ensuring security, placement of archives, archive officers, and control of archives is stated to be quite good, although there are still several things that need to be addressed. In the future, an officer on duty will need to know where documents are located so that it will be quicker and easier if at any time a document is needed.